Effect Of Substitution Of Ketapang Seed Flour (Terminalia Cattapa L) On The Quality Of Nastar - Mimi, Lusi Putri; Syarif, Wirnelis (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This study aims to analyze the effect of braided seed flour subtitute on the quality of nastar with the addition of braided seed flour as much as 15%, 30% and 45%. The study was conducted at the Tata Boga Workshop in October 2021.  This type of research is pure experimental research with a complete randomized design method (RAL) consisting of 4 treatments and 3 repetitions. The object of the study in this study was the addition of 15%, 30% and 45% braided seed flour. The free variable in this study was braided seed flour. The bound variable of the study is the quality of the resulting dumpling crackers covering shape, color, aroma, texture and taste. The analysis of data obtained from the oprganoleptic test involving 5 expert panelists, namely lecturers in Family Welfare Science, Padang State University.The data analysis technique used is Variant Analysis (ANAVA) to analyze sensory test data. The data that has been obtained is then tabulated in the form of tables and analyzed according to the test of each data.Then the data analysis is done, if the data obtained by Fhitung is greater than Ftabel then continued with duncan test. The results showed that the substitution of braided seed flour affects color, and has no effect on shape, aroma, texture and taste.Based on the best research results there is a treatment (X1) 15% with the category of round semicircular shape, uniform and neat shape, golden yellow color, fragrant aroma of cheese, crunchy texture and savory taste, therefore for further research it is recommended to use purple sweet potato flour with 15% substitution (X1) which produces good quality.